Organizational Support Perceived as a Predictor of Psychological Well-being among Employees at the Human Resource Development Center - Fenny Kurnia Azzahra; Rosita Endang Kusmaryani; Muhammad Zambri; Achmad Dheni (IJIP : Indonesian Journal of Islamic Psychology, 2025)
This study uses a quantitative approach with a survey method. The subjects of the study were 103 employees selected through a simple random sampling technique. The instruments used included the Perceived Organizational Support Scale (POSS-16) from Eisenberger et al. (1986) with 16 items, and Ryff's Psychological Well-Being Scale consisting of 18 items.  The results of the analysis showed that perceived organizational support had a significant effect on overall psychological well-being (p = 0.000; path coefficient = 0.713). More specifically, POS has a significant effect on five of the six dimensions of PWB, namely autonomy (path coefficient = 0.648; R² = 0.420), environmental mastery (path coefficient = 0.611; R² = 0.373), personal growth (path coefficient = 0.618; R² = 0.381), positive relations with others (path coefficient = 0.608; R² = 0.369), and purpose in life (path coefficient = 0.582; R² = 0.339). However, no significant effect of POS was found on the self-acceptance dimension. This finding confirms that perceived organizational support plays an important role in improving employee psychological well-being, especially in the five main dimensions of PWB. The results of the study provide important implications for organizational management, especially in designing strategies that encourage the creation of a supportive and conducive work environment for improving employee psychological well-being